Levinas, Durkheim, and the Everyday Ethics of Education. Issue 4 (20th March 2016) - Strhan, Anna
Abstract: This article explores the influence of Émile Durkheim on the philosophy of Emmanuel Levinas in order both to open up the political significance of Levinas's thought and to develop more expansive meanings of moral and political community within education. Education was a central preoccupation for both thinkers: Durkheim saw secular education as the site for promoting the values of organic solidarity, while Levinas was throughout his professional life engaged in debates on Jewish education and conceptualized ethical subjectivity as a condition of being taught. Durkheim has been accused of dissolving the moral into the social, and his view of education as a means of imparting a sense of civic republican values is sometimes seen as conservative, while Levinas's argument for an 'unfounded foundation' for morality is sometimes seen as paralyzing the impetus for concrete political action. Against these interpretations, I argue that their approaches present provocative challenges for conceptualizing the nature of the social, offering theoretical resources to deepen understanding of education as the site of an everyday ethics and a prophetic politics opening onto more compelling ideals for education than those dominant within standard educational discourses.